Validation Study of the Cirrhosis Acute Gastrointestinal Bleeding Score as Predictor Mortality in Patients with Liver Cirrhosis and Upper Gastrointestinal Bleeding - I Ketut Mariadi; Harris Hardian; Ajib Zaim Alamsyah; Ni Luh Putu Yunia Dewi; Putu Itta Sandi Lesmana Dewi; Ni Nyoman Gita Kharisma Dewi; Kadek Mercu Narapati Pamungkas; Gde Somayana; Komang Agus Wira Nugraha; Dwijo Anargha Sindhughosa; Mohamad Fadli bin Abd Rahman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
Background: The Cirrhosis Acute Gastrointestinal Bleeding (CAGIB) score was developed as a mortality predictor by integrating a range of clinical and laboratory parameters. This research seeks to validate the efficacy of the CAGIB score in predicting in-hospital mortality among cirrhotic patients experiencing upper gastrointestinal bleeding (UGIB) at Ngoerah Hospital.Methods: This study is a prospective observational study employing a validation test approach. A total of 161 patients diagnosed with liver cirrhosis and upper gastrointestinal bleeding (UGIB) at Ngoerah Hospital were enrolled. Receiver Operating Characteristic (ROC) analysis was utilized to evaluate the prognostic capability of the CAGIB score in predicting mortality and to identify the optimal cutoff point. Validation was conducted by assessing the CAGIB score's sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV).Results: The analysis of the CAGIB score as a predictor of mortality yielded an area under the curve (AUC) value of 0.83, with the optimal cutoff point determined at ≥ -4.66, based on the point farthest from the diagonal line on the ROC curve. The 95% Confidence Interval (CI) ranged from 0.777 to 0.897. Validation testing of the CAGIB score as a predictor of in-hospital mortality demonstrated a sensitivity of 80.8%, specificity of 70.5%, PPV of 69.4%, and NPV of 81.6%.Conclusion: The CAGIB score has been demonstrated to serve as a valid predictor of mortality, exhibiting commendable sensitivity and specificity, along with satisfactory positive and negative predictive values. The optimal cutoff points appropriately reflect the demographic and clinical characteristics of the cirrhosis patient population with UGIB at Ngoerah Hospital